The Effect of Acute Aerobic Exercise on Biomarkers of Renal Health and Filtration in Moderate-CKD - Forsse, Jeffrey S.; Peterson, Matthew N.; Papadakis, Zacharias; Taylor, J. Kyle; Hess, Burritt W.; Schwedock, Nicholas; Allison, D. Crawford; Griggs, Jackson O.; Wilson, Ronald L.; Grandjean, Peter W. (Research quarterly for exercise and sport, 2024)
Purpose: Efficacy of exercise to improve renal health and filtration remains understudied in adults with moderate-stages (stages G3a-b) of chronic kidney disease (CKD). Acute exercise may contribute clinically relevant information for exercise-related augmentation of renal health and filtration in CKD. Urine epidermal growth factor (uEGF) and cystatin C (CyC) are proposed to be more direct biomarkers of renal health and filtration. This study aimed to determine the influence of continuous moderate-intensity exercise (CMIE) and high-intensity interval exercise (HIIE) on traditional and novel biomarkers of renal health and filtration in moderate-stages of CKD. Methods: Twenty CKD participants completed 30 minutes of both CMIE and HIIE. Blood and urine samples were obtained pre, 1-hour, and 24-hours post-exercise. Traditional-serum creatinine (sCr) urine creatinine, novel-uEGF, uEGF ratio (uEGFr), and CyC. Estimates of glomerular filtration rate (eGFR)-modification of diet in renal disease (MDRD) and the CKD-Epidemiology (CKD-EPI)-responses were compared pre, 1 hr, and 24 hr post-exercise. Results: Relative to pre-exercise measures, uEGF remained unchanged in both exercise conditions. However, uEGFr was 5.4% greater 24-hours after HIIE (P = .05), while uEGFr remained unchanged with CMIE. sCr decreased 6 to 19% 1-hour post-exercise in both conditions (P = .009). On average renal filtration increased in eGFR-MDRD (7.2 ± 2.0 ml/min/1.73 m 2 ) (P = .007) and eGFR-CKD-EPI (8.6 ± 2.3 ml/min/1.73 m 2 ) 1-hour post-exercise (P = .009). Conclusion: By clinical estimates, renal filtration in CKD was not normalized but transiently improved regardless of exercise condition, with HIIE eliciting transient improvements in renal health.